ANALISIS PENCUCIAN UANG DALAM PERSPEKTIF EKONOMI ISLAM: ANTARA ETIKA DAN REGULASI - Muhammad Iltizam Hidayat; Haidar Naufal Fadhilah; Fadhilah Muhammad (Taksasila Edukasi Insani, 2025)
Money laundering is a financial crime that undermines economic stability and ethical standards, particularly when viewed through the lens of Islamic economics. This study aims to analyze money laundering from both ethical and regulatory perspectives, focusing on how Islamic values can complement positive law in combating financial crimes. Using a qualitative normative approach, the research relies on interpretative analysis of legal documents, Islamic economic principles, and scholarly articles. The findings reveal that the conventional legal system, while imposing strict penalties through laws such as Indonesia’s Law No. 8 of 2010, often lacks moral foundations, making enforcement less effective. Islamic economics offers a holistic alternative, emphasizing core values such as honesty (shiddiq), justice (‘adl), and accountability (amanah) in financial transactions. These principles not only prohibit illicit enrichment but also promote a transparent and fair economic system. Furthermore, the Islamic concepts of ta’zir and hisbah provide ethical sanctions that can support existing regulations. This integration of legal and spiritual frameworks presents a viable strategy for fostering a morally sound and legally robust financial system, aligned with the Islamic objective of maslahah (public welfare). Keywords : Money Laundering, Ethics,Islam, Regulasi